PROVIDING INTERDISCIPLINARY INTEGRATION AS A FACTOR INCREASING THE EFFICIENCY OF PRE-CONTROLLMENT MILITARY TRAINING - Agzamov Inom Salimjonovich (Journals Park Publishing, 2023)
In recent years, improving the quality and effectiveness of the education system in the country, forming modern knowledge and skills in kindergarten students, pupils and students, close cooperation between educational systems and the field of science and systematic work is being carried out to ensure integration, integrity and continuity of education.